Mobile news: what kinds of information needed by the youth? - Ahmad Ghazali, Akmar Hayati; Omar, Siti Zobidah (University of Lincoln, 2015)
Information can be obtained through various means and one of them is through mobile news (M-news). It is a new concept in searching for information. The information searching emphasis on individual’s ability to obtain information using devices such as smart phones with Internet access without being tied to a certain physical location. Thus, this study was undertaken to find out types of news chosen by youth through mobile news: and to identify the relationship between motivating factors in using mobile news with the youth acceptance. The results of the study show that the types of news chosen by youth through mobile news are crime and entertainment. Further, result of the Pearson’s correlation test shows that there is a positive and significant relationship between motivating factors in using mobile news and the youth acceptance. In conclusion, it is hoped that the mobile news could be one of the leading learning medium.